KARAKTER SARANG SEMUT PADA PERTANAMAN KAKAO DI JORONG SIDUAMPAN KECAMATAN RANAH BATAHAN KABUPATEN PASAMAN BARAT - Marina, Tama - (STKIP PGRI Sumbar, 2014)
Ant is a biological control agent that is efficient to cope like a pathogens, predators and parasitoids. Ants are know to the colonies and nests regular, consist of thousands ants per colony. Ant nests consist from rooms and paths. Ants build nests on plants for the activity, as a take shelter place from predators, and breeding place. Based on mentioned research has been about Character Ant Nests In Cocoa Planting In Jorong Siduampan Kecamatan Ranah Batahan Kabupaten Pasaman Barat. This research purpose to know the place character of ant nest, the size of ant nests and to know of environmental factors circles on the cocoa planting area cocoa. This research has been done in August and September 2014. This research used descriptive survey method using technique Hand Collecting, is sample removal in a direct by use hand and measure the nests. Based on the research has been found three kinds of ant nests, is the ants nest of Oecophylla smaragdina, ants nest of Dolichoderus sp., and Crematogaster rogenhofferi ant nest. Where the three kinds of ant nest possess character and size different, it is because of to eat factors and physical circles factors are temperature and humidity air.